2017
DOI: 10.3892/etm.2017.4067
|View full text |Cite
|
Sign up to set email alerts
|

Detection and analysis of hepatitis C virus in HIV-infected patients in the Guangxi province of China

Abstract: The aim of the present study was to investigate the prevalence rate of hepatitis C virus (HCV) infection in human immunodeficiency virus (HIV)-positive individuals and to study the infection status of HCV RNA in HIV-infected individuals who did not have anti-HCV antibodies in the Guangxi province of China, in order to provide basis for screening and clinical treatment of hepatitis C in future. Data were collected from patients recruited via a questionnaire. Between August 2008 and January 2009, 300 HIV-infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Our study findings were in accordance with the published studies [1,[12][13][14][15][16][17]. Sharma et al revealed that HBV/HIV infection was found in 11% while HCV/HIV was found in 13% of patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study findings were in accordance with the published studies [1,[12][13][14][15][16][17]. Sharma et al revealed that HBV/HIV infection was found in 11% while HCV/HIV was found in 13% of patients.…”
Section: Discussionsupporting
confidence: 93%
“…A study from Guangxi, China, revealed that 48.67% of patients with seropositive HIV also had HCV. Furthermore, the highest rate of anti‑HCV positivity was found in drug users [ 15 ]. Since HCV and HIV share similar transmission routes (blood transfusions, unprotected sexual intercourse, intravenous drug users, parenteral routes, perinatal routes (mother to child), and hemodialysis) coinfection of HIV/HCV is more common than HBV/HCV [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hepatitis B virus and HCV infections are known to be the common cause of chronic hepatitis and leading causes of liver-related deaths [3,4]. Both HBV and HCV have been implicated in liver cirrhosis and hepatocellular carcinoma [3][4][5][6], while HIV infection has been widely established to target and decrease the CD4 + cell, a glycoprotein found abundantly on the surfaces of regulatory T cells, T-helper cells, dendritic cells, monocytes and macrophages [7].…”
Section: Introductionmentioning
confidence: 99%
“…About 3% of the world population is reported to be infected with HCV [3,4]. Many risk factors have been documented to be associated with single, double and triple co-infection of these viruses [1,5,7,9]. The natural causes of HBV and HCV infections show variability among individuals [11] and all three viruses have been identified to share common routes of transmission [7,11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation